"Flowering Meadows", a result-oriented agri-environmental measure: Technical and value changes in favour of biodiversity. (July 2015) - Fleury, Philippe; Seres, Claire; Dobremez, Laurent; Nettier, Baptiste; Pauthenet, Yves
Highlights: We analyse the changes incurred by a result-oriented agri-environmental measure (AEM). We observe the development of a social norm in favour of biodiversity. Acceptance of result-oriented AEM by farmers is high. The changes of agricultural practices are limited. We discuss policy recommendations to improve the efficiency of result-oriented AEM. Abstract: Maintaining biodiversity in farming areas has become an important issue. Several public policies, including agri-environmental measures (AEMs), incite farmers to adapt their practices to preserve biodiversity. Yet many authors hold that farmers must undergo a cultural change by developing an environmental ethic and mind-set in order for these changes in practice to be sustainable. Looking at this issue from these two perspectives, via changes to practices and the values and influence of local social contexts, we analysed the implementation of a new result-oriented AEM: the "Flowering Meadows" AEM. Covering the Bauges, Haut-Jura and Vercors Regional Natural Parks in France, the survey was based on semi-structured interviews with farmers and other stakeholders such as environmentalists and local elected officials. We will show how the various actions accompanying this measure (training sessions, the "Flowering Meadows" competition, etc.) led to a consensus on the positive values of biodiversity. Although farmers committed to this measure for a variety of reasons (economic, environmental and social), most welcomed the idea of result-oriented payments, which they interpreted as a sign acknowledging their skills and knowledge. Changes to farming practices have nevertheless been limited to date. Here we show that the "Flowering Meadows" measure's innovation, together with the various actions to promote it, lies in its ability to build a positive social norm with respect to "meadow flowers, " seen as a symbol of biodiversity, rather than in its limited impact on changing farming practices. In conclusion, we discuss the potential of result-oriented agri-environmental schemes and their policy implications, as well as their outlooks. The particular way in which a result-oriented AEM is implemented is vital to its success in biodiversity conservation, and we make three recommendations for its improvement: anticipating a two-level payment structure better rewarding farmers who have improved biodiversity; paying particular attention to the formulation of a wording expressing the measure's finality in which all actors, not only environmentalists, may find their place; and keeping flexibility in the measure's implementation to account for the local context (existing networks of actors, intensity and quality of relations between farmers and other stakeholders). Instead of looking exclusively at the payment structure – that is, the result- and/or action-oriented AEM – our approach encourages a broad perspective on the conception of pro-biodiversity measures at the scale of an AEM scheme combining several actions: the AEM per se, plus other actions including training, education, advising and support for new governance processes.